The Main Source of National Philosophy: Turkism and Azerbaijanism - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2019)
The article investigates the sources of the idea of Azerbaijanism, which issimilar to Pan-Turkism, in the period of Azerbaijan Democratic Republic andbefore it and discusses the unity arising from its dual nature. The author showsthat the embryos of Azerbaijanism sourcing from historical memory are first revealed in the works of the 19th century thinkers A.A.Bakikhanov,M.F.Akhundzadeh, H. Zardabi, and further developed by A.Agaoglu,A.Huseynzade, A.Topchubashov, M.A.Rasulzadeh, J.Mammadquluzade,N.Yusifbeyli and others in the early 19th and 20th century as a synthesis of PanTurkism, Islamism and Modernity. In this sense, the article focuses on the ideasof integrity and identity of Azerbaijaniism and Pan-Turkism. At the same time,the article shows that Pan-Turkism and Azerbaijanism have recently becomethe main source of our national philosophy. Since the beginning of the 19th andearly 20th centuries, the main cores of our national philosophy were PanTurkism, Azerbaijanism, and Islamism. Today, these remain as the core ideasof national philosophy.The article shows that there is a serious need for grounding the setting thatconditioned the emergence of Azerbaijan Democratic Republic as well as thereasons for the selection of the name “Azerbaijan” for the newly establishedTurkic state and the the role of national ideologist M.A.Rasulzade concerningthese issues. One should know the moral-philosophical, political and historicalsignificance of the name of the state along with the literal meaning. In short,along with choosing the name of “Azerbaijan” for the new state and itsconnection with Pan-Turkism, Islamism and Modernity ideas should beinterpreted properly and the role it plays in our future political, historical, moraland philosophical life should be evaluated in the context of relevant historicaland philosophical setting.